Assessment of Drug Related Problems and Pharmacist Interventions in Inpatients with Cardiovascular Disease - S. M. Biradar; B. Kohima; V. Nayak; S. Nandikol; V. Warad; S. M. Byakod; B. S. Hunasagi; S. R. Awasthi (Рациональная фармакотерапия в кардиологии)
Aim. To identify and evaluate the nature and incidence of drug-related problems (DRPs) and to manifest the role of a pharmacist in ensuring safe and efficient use of medications with cardiovascular disease patients by using PCNE Classification to assess and report drug-related problems.Material and Methods. An Observational and Prospective study was conducted in a tertiary care hospital of medicine department of general and intensive/critical care units for a period of 6 months to identify and evaluate the nature and incidence of DRP’s and to manifest the role of a pharmacist in ensuring safe and efficient use of medications with cardiovascular disease patients by using PCNE Classification to assess and report drug-related problems.Results. Of 94 Patient profiles were evaluated out of which 78 (82.9%) patient profiles were identified with 208 DRPs. Among 208, 140 (67.3%) drug interactions, 15 (7.2%) untreated indication, 12 (5.8%) adverse drug reactions, 10 (4.8%) drug use without indication, 8 (3.8%) drug underused, 8 (3.8%) duration of treatment too short, 5 (2.4%) dose unclear, 4 (1.9%) inappropriate drug form, 3 (1.4%) duration of treatment too long, 2 (1.0%) too many drugs prescribed for an indication, 1 (0.5%) drug overused. For 208 DRPs identified and provided with 74 interventions which includes 30 (41.6%) drug discontinuation, 24 (33.3%) addition of a new drug, 4 (5.55%) change of dosage form, and 14 (19.4%) decrease the dose.Conclusion. The present study revealed that patients with cardiovascular diseases suffer from numerous DRPs that can be identified, resolved, or prevented to some extent by pharmacist intervention. Hence the study addresses the importance of clinical pharmacist in the management of DRPs among cardiovascular patients.